Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Given the following definition:

definition for /delta

How to proof these two equations?

How to proof this?

and

enter image description here

PS:

Actually, there are two proofs preceding the two(I have no problem with the following two), they are: enter image description here

Maybe they are hints on solving the latter two.

I encounter this problem here(section 2.1 about page 8~page 9)

share|improve this question

2 Answers 2

Let $X=Y=A$. We have $(\ast): \textrm{tr} XBY^TC = \textrm{tr} CXBY^T = \textrm{tr} (CXBY^T)^T = \textrm{tr} Y(CXB)^T$. So $$ \begin{eqnarray*} \nabla_A \textrm{tr} ABA^TC &=& \nabla_X \textrm{tr} XBY^TC + \nabla_Y \textrm{tr} XBY^TC \quad\textrm{(by chain rule)}\\ &=& \nabla_X \textrm{tr} X(BY^TC) + \nabla_Y \textrm{tr} Y(CXB)^T\quad(\textrm{by }(\ast))\\ &=& (BY^TC)^T + CXB = C^TAB^T + CAB \end{eqnarray*} $$ and we get the first result. The second result is more straightforward. Recall that for any fixed $i$, by Laplace expansion, we have $\det A=\sum_j (-1)^{i+j}A_{ij}M_{ij}(A)$, where $M_{ij}(A)$ denotes the $(i,j)$-minor of $A$. Since the computation of $M_{ij}(A)$ does not involve $A_{ij}$, we have $\frac\partial{\partial A_{ij}}\det A=(-1)^{i+j}M_{ij}(A)=C_{ji}(A)$, where $C_{kl}(A)$ denotes the $(k,l)$-cofactor of $A$. Hence $\nabla_A\det(A)=\textrm{adj}(A)^T=(\det A)(A^{-1})^T$.

share|improve this answer
    
thx, but can you explain what chain rule is? I think that is the obstacle for me to understand. –  xiaohan2012 Sep 26 '11 at 16:05
1  
Here chain rule means that for the function $g(X,Y)=\textrm{tr}XBY^TC$, we have $\frac{\partial g}{\partial a_{ij}} = \frac{\partial g}{\partial x_{ij}}\frac{dx_{ij}}{\partial a_{ij}} + \frac{\partial g}{\partial y_{ij}}\frac{dy_{ij}}{\partial a_{ij}}$. As $a_{ij}=x_{ij}=y_{ij}$, we get $\frac{\partial g}{\partial a_{ij}} = \frac{\partial g}{\partial x_{ij}} + \frac{\partial g}{\partial y_{ij}}$. This holds for each pair of $(i,j)$. Hence $\nabla_Ag=\nabla_Xg+\nabla_Yg$. –  user1551 Sep 26 '11 at 18:29

By writing it out in index notation (personal preference), the first equation is simple application of the product rule (see Einstein notation)

\begin{align} \nabla_{A_{ij}} \delta_{kl} A_{km}B_{mn} A^T_{np} C_{pl} = \newline \nabla_{A_{ij}} A_{km}B_{mn} A_{pn} C_{pk} = \newline (\nabla_{A_{ij}} A_{km})B_{mn} A_{pn} C_{pk} + (\nabla_{A_{ij}}A_{pn}) A_{km}B_{mn}C_{pk} = \newline (\delta_{ik}\delta_{jm})B_{mn} A_{pn} C_{pk} + (\delta_{ip}\delta_{jn}) A_{km}B_{mn} C_{pk} = \newline B_{jn} A_{pn} C_{pi} + A_{km} B_{mj} C_{ik} = \newline C^T\cdot A\cdot B^T + C\cdot A \cdot B \end{align}

as for the second equation, I've only seen it derived by rewriting $|A|$ in terms of its eigenvalues and doing some tricks or Jacobi's formula. I don't think the two preceding equations give you much to work with here.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.